Analysis of the Time Token Cooperative Learning Model to Improve the Speaking Skills of Elementary School Students - Zahra, Naila AZ; Bilkis, Ratu; Hafiza, Asra; Mutiara, Rizki Indah; Pebriana, Putri Hana (The Future of Education Journal, 2025)
This study aims to examine the effectiveness of the time token cooperative learning paradigm in improving elementary school students' speaking skills, particularly in the context of learning the Indonesian language. Communication skills are defined as the ability to engage in meaningful and beneficial exchanges with others. The time token cooperative learning model utilizes coupons or tokens to ensure active participation of all group members, provide each student with a fair opportunity to speak, and keep students focused on assigned tasks. This research was conducted using a literature review method, evaluating relevant sources published over the past five years. A total of 15 articles meeting the inclusion criteria were analyzed. The results indicate that implementing the time token cooperative learning model significantly helps elementary school students enhance their speaking fluency. These findings provide valuable insights for educators in Indonesia, offering an alternative and innovative approach to improve students' communication skills in teaching the Indonesian language at the elementary school level.